Fabrication of CDs hybrid MIL-68(In) derived In2O3In2S3 hollow tubular heterojunction and their exceptional self-powered PEC aptasensing properties for ampicillin detecting - Tao Yan; Yixuan Feng; Xiang Ren; Jinkai Li; Yizhong Lu; Meng Sun; Liangguo Yan; Qin Wei; Huangxian Ju (Journal of Materiomics, 2021)
A visible-light-driven self-powered photoelectrochemical (PEC) aptasensor was developed for ampicillin (AMP) detecting based on carbon dots (CDs) hybrid MIL-68(In)-derived In2O3In2S3 hollow tubular heterojunction (CDs/In2O3In2S3). In2S3 nanosheets uniformly grew in-situ on the surface of In2O3 hollow tubes, forming a close contact heterogeneous interface, which significantly promoted the transfer and separation of photo-generated carriers, and provided a large specific surface area and rich active sites for the PEC aptasensing platform. Furthermore, the CDs/In2O3In2S3/ITO electrode, which was obtained by dipping assembly, showed remarkable and stable photoelectric signals at zero-bias under visible light irradiation. The amino-functionalized AMP aptamer was fixed on the working electrode as a biological recognition element, and the concentration of AMP was determined by observing the change in photocurrent intensity caused by the specific capture of AMP molecules in solution. Under optimized conditions, the developed PEC aptasensor displayed a relatively wide linear range from 0.001 ng mL−1 to 300 ng mL−1, as well as a low detection limit (LOD) of 0.06 pg mL−1. Besides, the novel self-powered PEC AMP-aptasensor exhibited excellent reproducibility, good stability and selectivity, which open a potential avenue for antibiotic residues detection in environmental media.